Going technocratic? Diluting governing responsibility in electorally turbulent times. Issue 5 (29th July 2023) - Emanuele, Vincenzo; Improta, Marco; Marino, Bruno; Verzichelli, Luca
Abstract: Technocracy has recently triggered growing scholarly interest, especially as an alternative form of ruling to both party government and populism. In the context of weakened parties-citizens links and increasing external constraints faced by Western European ruling parties, technocratic appointments might help deal with the responsibility-responsiveness dilemma highlighted by Peter Mair. However, research on the explanatory factors of technocratic appointments is still underdeveloped. This article argues that the recourse to technocracy is fuelled by electoral volatility. In contexts of high electoral turbulence – and even more when parties frequently enter or exit the party system – ruling parties turn to technocratic appointments to dilute responsibility. This expectation is tested through an original longitudinal multilevel dataset including 655 cabinets and 373 elections in 20 Western European countries from 1945 to 2021. The findings of this article contribute to the current debate on technocracy and shed new light on the general understanding behind political representation.